Albania : Mining Sector Reform, Restructuring and Future Prospects - World Bank (World Bank, 2012)
This report provides a concise overview of the current situation of the mining sector in Albania. It evaluates the major events that took place in the last two decades (especially regarding the privatization process), and examines its governance, overarching policies and its legal frameworks that have guided the sector development. Having identified the weaknesses and difficulties that the sector faces, the report then suggests an outline for a comprehensive reform program. The main findings in this regard are related to: improving sector governance; improving regulatory effectiveness; strengthening the technical capacities; addressing environmental and social legacy, and community benefit sharing issues; and sustaining sector growth through sector promotion. The report also summarizes an evaluation of the mineral legal and regulatory environment, in order to inform an overall reform strategy and to identify commodities and/or resource areas of particular interest going forward, 'low hanging fruit' that might offer new growth opportunities. The overall conclusion of the report is that sector reform should emphasize new Greenfield resource potential through generative exploration by smaller and medium-sized international 'junior' mining companies. New resource development will be undertaken within a strengthened governance framework reinforced by a competitive, transparent, stable, non-discretionary regulatory regime. Although now highly fragmented, existing operations will be improved with the introduction of new operations performing to international good practice. Additionally, the private sector should be enabled to consolidate license holdings under improved regulatory enforcement that prevents licenses being held for speculation without intention to undertake meaningful investments that will result in development.